2017
DOI: 10.2118/175892-pa
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Effective Fracture Pore Volume From Flowback Data and Evaluating Its Relationship to Design Parameters of Multistage-Fracture Completion

Abstract: Summary Flowback data from seven multifractured horizontal tight oil/gas wells in Anadarko Basin show two separate regions during the single-phase water production. Region 1 shows a dropping casing pressure, and Region 2 shows a flattening casing pressure. This paper investigates the flowback behavior of the two regions, and illustrates how flowback data can be interpreted to estimate effective fracture pore volume, and to investigate its relationship to completion-design parameters. We construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Pressure data from diagnostic fracture injection test (DFIT) can be used to determine representative matrix permeability, minimum in-situ stress, characterize the roughness of fracture walls and estimate the pressure/stress dependent conductivity of un-propped fractures (Wang and Sharma 2017;. Flow back data can also be useful to infer effective fracture pore volume if fracture compliance can be estimated from DFIT (Fu et al 2017). The data of stretched transitional flow period can possibly yield information on fracture complexity and heterogeneity (Jorge 2016;.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure data from diagnostic fracture injection test (DFIT) can be used to determine representative matrix permeability, minimum in-situ stress, characterize the roughness of fracture walls and estimate the pressure/stress dependent conductivity of un-propped fractures (Wang and Sharma 2017;. Flow back data can also be useful to infer effective fracture pore volume if fracture compliance can be estimated from DFIT (Fu et al 2017). The data of stretched transitional flow period can possibly yield information on fracture complexity and heterogeneity (Jorge 2016;.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture networks in shale can be quite complex due to the reactivation of natural fractures by hydraulic fracturing. Also, studies suggest that most fracturing water remains in natural fractures after the fracturing treatment [47,87]. The results of temperature change may thus be influenced by the simplified fracture geometry for shale gas wells.…”
Section: Limitations and Recommendation For Future Studiesmentioning
confidence: 99%
“…The results of his simulations indicated that the closure of unpropped fractures within fracture networks resulted in low water recovery. Fu et al [25] collated and processed the early flowback data of seven multi-fractured horizontal wells in tight reservoirs. Data analysis suggested that most of the facture systems were un-propped after stimulation and held most of the fracturing water.…”
Section: Introductionmentioning
confidence: 99%